Th-2 signature in chronic airway diseases: towards the extinction of asthma−COPD overlap syndrome?. Issue 5 (2nd May 2017) - Cosío, Borja G.; Pérez de Llano, Luis; Lopez Viña, Antolin; Torrego, Alfons; Lopez-Campos, Jose Luis; Soriano, Joan B.; Martinez Moragon, Eva; Izquierdo, Jose Luis; Bobolea, Irina; Callejas, Javier; Plaza, Vicente; Miravitlles, Marc; et al.
We aimed to describe the differences and similarities between patients with chronic obstructive airway disease classified on the basis of classical diagnostic labels (asthma, chronic obstructive pulmonary disease (COPD), or asthma–COPD overlap (ACOS)) or according to the underlying inflammatory pattern (Th-2 signature, either Th-2-high or Th-2-low). We performed a cross-sectional study of patients aged ≥40 years and with a post-bronchodilator forced expiratory volume in 1 s to forced vital capacity ratio ≤0.7 with a previous diagnosis of asthma (non-smoking asthmatics (NSA)), COPD or ACOS, the latter including both smoking asthmatics (SA) and patients with eosinophilic COPD (COPD-e). Clinical, functional and inflammatory parameters (blood eosinophil count, IgE and exhaled nitric oxide fraction ( F eNO )) were compared between groups. Th-2 signature was defined by a blood eosinophil count ≥300 cells·μL −1 and/or a sputum eosinophil count ≥3%. Overall, 292 patients were included in the study: 89 with COPD, 94 NSA and 109 with ACOS (44 SA and 65 with COPD-e). No differences in symptoms or exacerbation rate were found between the three groups. With regards the underlying inflammatory pattern, 94 patients (32.2%) were characterised as Th-2-high and 198 (67.8%) as Th-2-low. The Th-2 signature was found in 49% of NSA, 3.3% of patients with COPD, 30% of SA and 49.3% of patients with COPD-e. This classification yielded significant differences in demographic, functional and inflammatory characteristics. We conclude that a classification based upon the inflammatory profile, irrespective of the taxonomy, provides a more clear distinction of patients with chronic obstructive airway disease. Identifying a Th-2 signature in patients with chronic airflow limitation effectively differentiates treatable traits http://ow.ly/kq1E309MMkt